The Effect of Accounts Receivable and Inventory on Profits in Large Trading Subsector Companies Listed on the Indonesian Stock Exchange in 2017-2021 - Juwita, Amelia; Mursalini, Wahyu Indah; Nurhayati, Nurhayati; Hendrayani, Eka (Transpublika Publisher, 2024)
The main aim of this study is to investigate how accounts receivable and inventory influence the profitability of companies in the Large Trade subsector that are listed on the Indonesia Stock Exchange between 2017 and 2021. A total of 47 companies were examined in this research, with 16 companies chosen for the sample using purposive sampling. Quantitative data was employed for the analysis. The results indicated that there was no significant relationship between accounts receivable and profits, as the t-value of -0.154 was found to be lower than the t-table of 1.771, with a significance level of 0.878 > 0.05. Hence, the theory concerning accounts receivable was disapproved in this investigation. Conversely, stock was discovered to have a considerable effect on earnings with a t-value of 1.830, surpassing the t-table of 1.771, and significance level of 0.032 < 0.05, leading to the affirmation of the theory concerning inventory. Additionally, upon inspecting both accounts receivable and inventory together, there was a notable combined impact on earnings, as indicated by an F-value of 1.719 > F-table 1.611 and a significance of 0.018 < 0.05. Consequently, the hypothesis pertaining to the simultaneous influence of both variables on profit was acknowledged. The research equally found that about 23% of the variability in profit can be clarified by accounts receivable and inventory, whereas the other 77% is affected by unexplored factors like earnings manipulation, stock prices, and financial management proficiency.